Challenges and Advancements in Protection of DC Microgrid System-A Comprehensive Review. Issue 4 (21st December 2022) - Kumar Prince, Satyavarta; Prasad Panda, Kaibalya; Naayagi, R.T.; Sanjeevikumar, P.; Khan, Baseem; Affijulla, Shaik; Panda, Gayadhar
ABSTRACT: Microgrids have recently gained popularity in the industry and research communities due to the potential use of photovoltaic (PV), wind, and battery-based energy systems. The use of bidirectional DC-DC converters as active interconnected devices allows for power regulation between DC microgrids with high flexibility. In general, DC microgrids are more effective, reliable, and advantageous than AC microgrids because of the simplicity in the control techniques, which can also provide resilience to the utility grid. Moreover, DC microgrid systems have significant variations in short-circuit levels between grid-integrated (i.e. 5–10 times the rated current) and isolated (i.e. 2–3 times of rated current) modes of operation, which leads to blind protection, a lack of natural zero-crossing current, and false tripping. This paper discusses the comparative analysis on various protection challenges in DC microgrid due to the integration of distributed energy supplies, converters, and storage units. The protection system is critical due to the unique characteristics of faults in a DC microgrid. Thus, a systematic approach is presented in this paper related to various topologies, fault and protection challenges, and other issues in the DC distribution system. Further, grounding and lack of zero-crossing current issues in DC microgrids are closely investigated. Moreover, the difficulties associated with the grounding system in DC microgrids are discussed, along with the characteristics of various grounding topologies. Usually, the conventional protection scheme is ineffective in most cases for DC microgrid. Hence, a thorough review is performed with simulation of various protection schemes in MATLAB/Simulation platform; the results reveal that the adaptive protection scheme is most successful for the DC microgrid. In future research, DC microgrid protection in grid-connected and island mode may be for fault detection and isolation mechanism to enhance the reliability of the electric grid.